2015
DOI: 10.1016/j.bbabio.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling, metabolic inhibition and induction of mitochondrial permeability transition in rat liver mitochondria caused by the major long-chain hydroxyl monocarboxylic fatty acids accumulating in LCHAD deficiency

Abstract: Patients with long-chain 3-hydroxy-acyl-CoA dehydrogenase (LCHAD) deficiency commonly present liver dysfunction whose pathogenesis is unknown. We studied the effects of long-chain 3-hydroxylated fatty acids (LCHFA) that accumulate in LCHAD deficiency on liver bioenergetics using mitochondrial preparations from young rats. We provide strong evidence that 3-hydroxytetradecanoic (3HTA) and 3-hydroxypalmitic (3HPA) acids, the monocarboxylic acids that are found at the highest tissue concentrations in this disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…Noteworthy, morphological mitochondrial alterations in skeletal muscle detected by magnetic resonance imaging, as well as increased blood levels of creatine phosphokinase and lactic acid associated with episodic rhabdomyolysis, were found in VLCAD-deficient patients [23,24], suggesting a disturbance of mitochondrial energy homeostasis, although, to the best of our knowledge, ATP production was not measured in these patients. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29]. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, morphological mitochondrial alterations in skeletal muscle detected by magnetic resonance imaging, as well as increased blood levels of creatine phosphokinase and lactic acid associated with episodic rhabdomyolysis, were found in VLCAD-deficient patients [23,24], suggesting a disturbance of mitochondrial energy homeostasis, although, to the best of our knowledge, ATP production was not measured in these patients. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29]. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Their final concentrations in the incubation medium were in the range 10–60 μ m , whereas the EtOH concentration was always 1%. The chosen doses were previously used in other studies investigating the effects of the long‐chain fatty acids on biochemical parameters and are similar to those found in plasma of the affected patients . The same percentage of EtOH was present in controls and was found not to alter per se the parameters evaluated.…”
Section: Methodsmentioning
confidence: 84%
“…These findings are probably related to the marked decrease of ATP formation caused by 3HTA and 3HPA in the heart. On the other hand, we cannot rule out the possibility that the decrease of mitochondrial reducing equivalents and ΔΨm provoked by of 3HTA and 3HPA in the absence of exogenous Ca 2+ were at least partly a result of the uncoupling behavior of these fatty acids .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In vitro studies with CsA have reinforced findings from genetic knockout/knockdown by showing that cyclophilin inhibition can protect mitochondria from the kinds of metabolic disturbances that occur in NASH. For example, CsA blocked mPT in liver mitochondria following application of short-, medium-, and long-chain fatty acids or lysophosphatidylcholine [118][119][120][121]; blocked mPT and significantly reduced mitochondrial ROS, ATP depletion, and death of preadipocytes induced by high fatty acid concentrations [122]; blocked mPT and significantly reduced fructose-induced or high glucose-induced death of INS-1 pancreatic islet cells [123]; blocked mPT and restored the ATP deficit induced by long-chain fatty acids or palmitoyl-L-carnitine in cardiac mitochondria [124][125][126][127][128]; blocked mPT and prevented palmitate-induced insulin resistance in muscle mitochondria [107]; blocked hepatocyte death resulting from high glucose and hydrogen peroxide [129]; and alleviated fatty acid-induced ER stress gene induction, ROS elevation, and death of LO2 hepatocytes [60,130]. Düfer et al (2001), in contrast, found that CsA diminished glucose-induced insulin secretion of mouse pancreatic islets in vitro by inhibiting glucose-stimulated oscillations of the cytoplasmic free calcium concentration [131].…”
Section: Cyclophilin Involvement In Mitochondrial Metabolismmentioning
confidence: 99%